Isotopic and diagenetic constraints of the neoproterozoic Villa Mónica and Loma Negra formations, Tandilia System, Argentina - First results - Gómez Peral, Lucía Elena (2003)
The objective of this case study in Argentine Neoproterozoic successions is twofold. On one hand we want to add stable isotope data combined embedded in a diagenetic study to correlate these outcrops with similar lithologies of the Neoproterozoic world-wide. The Tandilia System is a 350 km long, northwestsoutheast orientated orographic belt, located in the Province of Buenos Aires, which is comprised by an igneous metamorphic basement and a Neoproterozoic to Lower Palaeozoic sedimentary coyer. In the Olavarria area, this Neoproterozoic sedimentary succession is composed of the Villa Monica, Cerro Largo and Loma Negra formations (Sierras Bayas Group) and the Cerro Negro Formation (Poiré, 1993; see Fig. 2). These lithostratigraphic units were grouped into four depositional sequences: Tofoletti (1), Malegni (II) Villa Fortabat (III) and La Providencia (IV) sequences (Spalletti and Poiré, 2000).